Does Collateral Affect the Access and Loan Payment Behavior of MSMEs? - Lanang Tanu Prihantoro; Chaikal Nuryakin (Journal of Economics, Business, and Accountancy Ventura, 2020)
Various problems regarding the distribution of revolving funds at the Ministry of Cooperatives and SMEs have prompted the government to transfer its management through LPDB-KUMKM (Revolving Fund Management Institution for Cooperatives and MSMEs) for the sake of financial accountability and professionalism. Several improvements have been made, among others, through collateral and service rates that have never been applied before. The service rate was applied first, with a value lower than the bank interest rate. This study examines the impact of collateral and service rates on the loan default rates. This study uses data of loan developments of LPDB-KUMKM partners from the beginning to 2018. The Logit Regression Model is used to support the analysis. This study's results indicate that collateral has a negative correlation with the growth in loan default rates. This study's results are expected to be taken into consideration by the government in regulating financing needs, especially regarding collateral and service rates, so that the accessibility of MSMEs to obtain financing from LPDB-KUMKM will increase.